The influence of financial literacy and the ability to prepare financial reports on the financial performance of micro, small and medium enterprises (UMKM) in Matani II District, Tomohon City - Hutabarat, Yeni Rosalina; Tangkau, Jaqueline E.M; Tala, Olifia Yodiawati (Yayasan Widyantara Nawasena Raharja, 2025)
The purpose of this study was to find out how the influence of Financial Literacy and the Ability to Prepare Financial Statements on the Financial Performance of Micro, Small and Medium Enterprises (UMKM) in Matani II District, Tomohon City. This type of research is a quantitative method by processing primary data. The type of sample in this study is purposive sampling. The population and sample in this study are 37. The analysis in this study is multiple linear regression The results of the study show that Financial Literacy does not have a positive and significant effect on the Financial Performance of Micro, Small and Medium Enterprises (UMKM), while the Ability to Prepare Financial Statements has a positive and significant effect on the Financial Performance of Micro, Small and Medium Enterprises (UMKM) in Matani II Village, Tomohon City.